Pertanggungjawaban Hukum Pelaku Tindak Pidana oleh Penderita Gangguan Disabilitas Intelektual Alzheimer - Antoneo, Brian Rico Teddy; Setyorini, Erny Herlin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The New Criminal Code (Article 39 of Law of 2023) states that perpetrators of criminal acts who, due to severe mental disorders or impaired thinking, are unable to realize the consequences of their actions, will not be punished. This study examines the application of this provision to murder perpetrators suffering from Alzheimer's. Due to its neurodegenerative nature, moderate-to-severe Alzheimer's disease organically eliminates mens rea, thus fulfilling the grounds for expungement. However, if there is prior negligence (neglect for treatment while still conscious), liability based on culpa can still be imposed. The study found disparities in judges' decisions due to loose interpretations and inconsistent psychiatric post-mortem examinations. It is recommended: (1) official guidelines for the interpretation of Article 39, (2) standardization of forensic examinations, and (3) the application of therapeutic sanctions in the form of mandatory treatment plus security (maatregel TBS) as an alternative to imprisonment, in order to achieve a balance of justice between the protection of ODGJ and the rights of victims.